FLT3-TKD in the prognosis of patients with acute myeloid leukemia: A meta-analysis - Li, Shuping; Li, Na; Chen, Yun; Zheng, Zhihua; Guo, Yao (Frontiers in Oncology, 2023)
Abstract Background Fms-like tyrosine kinase 3 (FLT3) gene mutations occur in approximately 30% of all AML patients. Internal tandem duplication (ITD) in the juxtamembrane domain and point mutations within the tyrosine kinase domain (TKD) are two distinct types of FLT3 mutations. FLT3-ITD has been determined as an independent poor prognostic factor, but the prognostic impact of potentially metabolically-related FLT3-TKD remains controversial. Hence, we performed a meta-analysis to investigate the prognostic significance of FLT3-TKD in patients with AML. Methods A systematic retrieval of studies on FLT3-TKD in patients with AML was performed in PubMed, Embase, and CNKI databases on Sept. 30th, 2020. Hazard ratio (HR) and its 95% confidence intervals (95% CIs) were used to determine the effect size. Meta-regression model and subgroup analysis were used for heterogeneity analysis. Begg’s and Egger’s tests were performed to detect potential publication bias. The sensitivity analysis was performed to evaluate the stability of findings in meta-analysis. Results Twenty prospective cohort studies (n=10970) on the prognostic effect of FLT3-TKD in AML were included: 9744 subjects with FLT3-WT and 1226 subjects with FLT3-TKD. We found that FLT3-TKD revealed no significant effect on DFS (HR=1.12, 95% CI: 0.90-1.41) and OS (HR=0.98, 95% CI: 0.76-1.27) in general. However, meta-regressions demonstrated that patient source contributed to the high heterogeneity observed in the prognosis of FLT3-TKD in AML. To be specific, FLT3-TKD represented a beneficial prognosis of DFS (HR=0.56, 95% CI: 0.37-0.85) and OS (HR=0.63, 95% CI: 0.42-0.95) for Asians while it represented an adverse prognosis of DFS for Caucasians with AML (HR=1.34, 95% CI: 1.07-1.67). Conclusion FLT3-TKD revealed no significant effects on DFS and OS of patients with AML, which is consistent with the controversial status nowadays. Patient source (Asians or Caucasians) can be partially explained the different effects of FLT3-TKD in the prognosis of AML patients.